Localized thickened flame model for stretched premixed flames - Cui, Tongtong; Terashima, Hiroshi; Kawai, Soshi (Combustion and flame, 2025)
This study presents a novel thickened flame model called the LTF-S model (localized thickened flame model for stretched premixed flames) to predict premixed flame propagation under stretching effects accurately. The LTF-S model constructs unresolved scale terms of spatially filtered governing equations, ensuring proper flame resolution and accurate capture of both the unstretched flame speed and the effects of stretching on the flame speed. The model’s accuracy is confirmed through validation with a cylindrically propagating premixed flame problem and a flame-vortex interaction problem. The validation results demonstrate that the LTF-S model effectively predicts the correct flame behavior under stretching effects, even with coarse grid resolutions. Novelty and Significance Statement: This study proposes a novel thickened flame model, the LTF-S model (localized thickened flame model for stretched premixed flames), designed to accurately predict premixed flame propagation under stretching effects. The novelty of this model lies in the construction of unresolved scale terms in the spatially filtered governing equations, ensuring proper flame resolution and accurate capture of both the unstretched flame speed and the effects of stretching on the flame speed. The model employs a linear relationship between stretched flame speed and stretch rate, with the Markstein length as the proportionality constant, to construct the unresolved scale terms associated with stretching effects. The LTF-S model differs significantly from existing TF-based models that rely on a Lewis number correction. Most of the primary non-dimensional numbers in the problem, including the Lewis number, are retained in the LTF-S model. The significance of the LTF-S model is demonstrated by its successful application in simulations of cylindrically propagating premixed flames and flame-vortex interactions. When compared with direct numerical simulation (DNS) results, the LTF-S model accurately predicts flame behavior under stretching effects, even with coarser grid resolutions. This study represents a significant advancement in premixed flame modeling for combustion large-eddy simulations (LES). •A novel thickened flame model, the LTF-S model, is proposed for stretched premixed flames.•Unresolved terms are constructed to recover correct stretched flame speeds under flame thickening.•Markstein length ratio introduced plays a key role in retrieving stretching effects on flame speeds.•The capability of the LTF-S model is demonstrated through canonical stretched flame simulations.